2006
DOI: 10.1007/s00439-006-0263-5
|View full text |Cite
|
Sign up to set email alerts
|

Fibrillin I gene polymorphism is associated with tall stature of normal individuals

Abstract: In order to test the hypothesis that polymorphisms of the Marfan syndrome gene (FBN1) might affect the stature (height) of normal individuals, we genotyped three exonic SNPs on 428 males, 219 with tall stature (>2 SD) and 209 with normal stature (within +/-1 SD). One of the SNPs, rs8033037, in exon 15 showed a significant correlation (P = 0.0061) with the adult height, suggesting that FBN1 is one of the 'stature genes' of normal individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Additionally, of these three SNPs, rs25458 (p.Asn625Asn, c.1875 T > C) is known to cause a same-sense mutation of asparagine in a highly conserved domain of the cb EGF-like #6. Furthermore, a previous study showed that the mutant C allele at Asn625 was significantly overrepresented in the ''tall stature group,'' suggesting that the Asn625 polymorphism is significantly correlated with adult height [12].…”
Section: Discussionmentioning
confidence: 97%
“…Additionally, of these three SNPs, rs25458 (p.Asn625Asn, c.1875 T > C) is known to cause a same-sense mutation of asparagine in a highly conserved domain of the cb EGF-like #6. Furthermore, a previous study showed that the mutant C allele at Asn625 was significantly overrepresented in the ''tall stature group,'' suggesting that the Asn625 polymorphism is significantly correlated with adult height [12].…”
Section: Discussionmentioning
confidence: 97%
“…However, since FBN1 polymorphisms had been associated with tall stature, and isolated scoliosis in non-Marfan patients, clinical variability may be implied by allelic variants in FBN1 expression or by certain FBN1 polymorphisms [ 38 ]. Alternatively, modifier genes, such as TGF-β and FBN2 , or even polymorphisms located in the FBN1 gene may influence the penetrance or severity of MFS [ 39 ]. Therefore, involved mechanisms affecting the R2627W FBN1 variant expression could be similar, and its penetrance may rely on the presence of other variants in FBN1 or other genes involved in the same pathway as suggested by Van Dijk et al [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…one or a few [97][98][99], is FBN2 (5q23-q31) [33]. The gene used for Marfan Syndrome, which can include symptoms such as tall, thin, long fingers, scoliosis, and mitral valve prolapse [8,99,100], is FBN1 (15q21.1) [7]. individuals with PE).…”
Section: Pedigree Construction Pe-inheritance and Sex Ratiomentioning
confidence: 99%